Bioeficácia de fontes de metionina em dietas de frangos de corte - Mencalha, Raquel (2016)
This study aimed to determine the relative bioavailability of Lmethionine sources 99% , DL- methionyl -DL -methionine 97 % compared to the DL- methionine 99% in the initial stages and growth of broilers receiving based diets corn and soybean meal. Two performance experiments were carried out in phases 1-21 days and 22-42 days of age using in total 1750 chicks (Cobb - 500) were randomly divided into ten treatments (7 repetitions / 25 birds). three methionine sources were used at three levels of supplementation and one without methionine supplementation treatment. The corn-based diets and soybean meal for both experiments were isocaloric and isoproteic, varying only the methionine + cysteine and methionine sources. They evaluated the performance, breast yield and carcass yield. At 21 and 42 days were killed two birds per repetition, to 21 for breast yield and 42 for breast and carcass yield. The bioavailability relative to weight gain, feed conversion and breast yield were obtained using the slope-ratio methods, multiple linear regression and exponential regression. The results were submitted to analysis of variance and means were compared by the SNK test (P < 0.05). There was no effect of methionine sources on carcass characteristics (P> 0.05). Based on the exponential regression method and using the DL-methyl as a standard, the mean bioavailability for L-met and DL-met-met were 92.02 and 105.54 %, respectively, for the initial phase of broilers and for final cutting phase were 90.5 and 105.5 % based on the average bioavailability of weight gain and feed conversion. Regarding breast yield, a higher bioavailability for DL-met -met in the first phase (119%) and the final stage L- met showed better bioavailability (118%).